2020
DOI: 10.1002/chem.202001802
|View full text |Cite
|
Sign up to set email alerts
|

Nanogels with Selective Intracellular Reactivity for Intracellular Tracking and Delivery

Abstract: Am ultimodal approach for hydrogel-based nanoparticles was developed to selectively allow molecular conjugated species to either be released inside the cell or remain connected to the polymer network. Using the intrinsic differencei nr eactivity between esters and amides, nanogels with an amide-conjugated dye could be trackedintracellularlyl ocalizingnext to the nucleus, while ester-conjugation allowed for liberation of the molecular speciesf rom the hydrogeln etwork inside the cell, enabling delivery througho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…It is noteworthy that the fluorescein moieties in our PNIPAM-fluorescein were conjugated to the PNIPAM chains through ester bonds. Zu et al found that the fluorescein moieties can be released from the PNIPAM chains through cleavage of the ester bonds by esterase in endosomes of live cells, and the released fluorescein molecules enter the cytoplasm of the cells, exhibiting diffuse fluorescence . We did not observe fluorescein fluorescence in the cytosol of the three microparticle-containing macrophages in Figure C1.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…It is noteworthy that the fluorescein moieties in our PNIPAM-fluorescein were conjugated to the PNIPAM chains through ester bonds. Zu et al found that the fluorescein moieties can be released from the PNIPAM chains through cleavage of the ester bonds by esterase in endosomes of live cells, and the released fluorescein molecules enter the cytoplasm of the cells, exhibiting diffuse fluorescence . We did not observe fluorescein fluorescence in the cytosol of the three microparticle-containing macrophages in Figure C1.…”
Section: Resultsmentioning
confidence: 83%
“…Zu et al found that the fluorescein moieties can be released from the PNIPAM chains through cleavage of the ester bonds by esterase in endosomes of live cells, and the released fluorescein molecules enter the cytoplasm of the cells, exhibiting diffuse fluorescence. 20 We did not observe fluorescein fluorescence in the cytosol of the three microparticle-containing macrophages in Figure 3C1 the phagosomes contained esterase, this result suggests that the released fluorescein molecules were confined in the phagosomes. Figure 3C2 shows the same area as Figure 3C1 2 min after replacing the medium with 0 °C PBS.…”
Section: Characterization Of Microparticlesmentioning
confidence: 71%
“…The hydrophilic nature of the hydrogel facilitates uses in vivo due to the presence of numerous polar groups such as –OH, –COOH, –CONH 2 and –SO 3 H distributed along the polymer chain [ 41 , 113 ]. Besides, to facilitate the renal clearance of the final degraded products, many labile cross-links have been introduced in the chemical design of nanogels such as hydrazone, disulfide, carbonate ester, and siloxane to develop degradable nanogels [ 82 , 99 , 114 , 115 ]. Besides, nanogels composed of natural biodegradable polymers such as chitosan, pullulan, dextran, hyaluronic acid, alginate, and gelatin can be degraded by biological microenvironments [ 99 ].…”
Section: Synthesis Properties and Biocompatibility Of Nanogelsmentioning
confidence: 99%
“…[ 13 ] A nGel is a highly cross‐linked nanometer‐sized hydrogel particle [ 14,15 ] that has been used in many systems as responsive nanomaterial due to the possibility of incorporating thermoresponsive properties, [ 16–18 ] but also responding toward pH, [ 19 ] light, [ 20 ] or redox chemistry. [ 21 ] Additionally, due to the hydrogel properties these particles are also of interest as carriers for delivery [ 22–25 ] of drugs or other biological molecules and proteins [ 25 ] that may be applied in regenerative medicine, [ 26 ] biosensing, and intracellular detection. [ 27 ] Therefore, surface coatings derived from nGels, with the possibility of implementing the aforementioned functions, provide the opportunity to develop new advanced biomedical coatings that takes its place among the often‐used polymer brush coatings and conventional hydrogel coatings.…”
Section: Introductionmentioning
confidence: 99%